Dukungan Sosial Rekan Kerja dan Atasan dengan Burnout Pada Aparatur Sipil Negara - Akbar, Muhammad Taufik; Soetjiningsih, Christiana Hari (Bulletin of Counseling and Psychotherapy, 2022)
The demands of the Civil Servants who always optimally carry out their duties to serve the community cause them to be vulnerable to work stress. Sustained work stress on the Civil Servants can result in burnout or boredom at work for the employee. One of the factors that influence the occurrence of burnout is social support. Therefore, this study will examine the relationship between social support from colleagues and superiors and burnout in the Civil Servants in two Salatiga city government agencies. The method used in this research is a quantitative approach with a correlational design. Participants in this study were all Civil Servants in two Salatiga City Government agencies, totaling 150 employees. The sampling technique used in this research is saturation sampling technique. This research instrument uses a scale of social support and burnout scale. This data analysis uses the Rank Spearman correlation test. This study's results indicate a significant negative relationship between social support and burnout in civil servants in two Salatiga City Government agencies. This can be seen from the Rank Spearman correlation value of -0.412 with a Sig. (1-tailed) of 0.000 Sig. (1-tailed) of 0.05. The results of this study indicate that the higher the social support, the lower the level of burnout in the Civil Servants in the two Salatiga City Governments. Conversely, the lower the level of social support for the Civil Servants in the two Salatiga City Government agencies, the higher the burnout rate.